Consumption of calcium-fortified cereal bars to improve dietary calcium intake of healthy women: randomized controlled feasibility study. - Jennifer T Lee; Carolyn E Moore; John D Radcliffe (PLoS ONE)
Unlabelled Calcium is an important structural component of the skeletal system. Although an adequate intake of calcium helps to maintain bone health and reduce the risk of osteoporosis, many women do not meet recommended daily intakes of calcium. Previous interventions studies designed to increase dietary intake of women have utilized primarily dairy sources of calcium or supplements. However, lactose intolerance, milk protein allergies, or food preferences may lead many women to exclude important dairy sources of dietary calcium. Therefore, we undertook a 9 week randomized crossover design trial to examine the potential benefit of including a non-dairy source of calcium in the diet of women. Following a 3 week run-in baseline period, 35 healthy women > 18 years were randomized by crossover design into either Group I or Group II. Group I added 2 calcium-fortified cereal bars daily (total of 400 mg calcium/day) (intervention) to their usual diet and Group II continued their usual diet (control). At the end of 3 weeks, diets were switched for another 3 weeks. Intakes of calcium and energy were estimated from 3-day diet and supplemental diaries. Wilcoxon signed-rank tests were used for within group comparisons and Mann Whitney U tests were used for between group comparisons of calcium and energy intake. Dietary calcium was significantly higher during intervention (1071 mg/d) when participants consumed 2 calcium-fortified cereal bars daily than during the baseline (720 mg/d, P <0.0001) or control diets (775 mg/d, P = 0.0001) periods. Furthermore, the addition of 2 calcium-fortified cereal bars daily for the 3 week intervention did not significantly increase total energy intake or result in weight gain. In conclusion, consumption of calcium-fortified cereal bars significantly increased calcium intake of women. Further research examining the potential ability of fortified cereal bars to help maintain and improve bone health of women is warranted. Trial registration ClinicalTrials.gov NCT01508689.